Oral Candidal Carriage and its Correlation with Salivary Oxidative Stress in Smokeless Tobacco Users - Zeeshan Kamal, Muhammad Shahzad, Tahir Ali Khan, Falak Niaz, Kajal Hayat (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Smokeless tobacco use, particularly the consumption of Naswar, is prevalent in Pakistan and has been associated with various chronic diseases, including oral cancer. Naswar is known to contain toxic heavy metals, carcinogenic substances, and microbial contaminants. This study aims to assess the oral Candida carriage and biofilm formation in Candida albicans isolates from Naswar users and its association with salivary oxidative stress. Methods: A cross-sectional study was conducted involving 150 participants, divided into Naswar users (n=75) and Non-users (n=75). Socio-demographic data, oral health, hygiene practices, and Naswar usage patterns were collected through a standardized questionnaire. Salivary samples were collected, and Candida strains were identified using culture techniques. Salivary oxidative stress was assessed using a DPPH solution-based free radical system. Results: The mean age of participants was 30 ± 7.3 years for Naswar users and 30.2 ± 7.1 years for non-users. No significant differences were observed in oral health and hygiene practices between the two groups. Among Naswar users, the most common type of product used was green moist Naswar (77.3%). Oral Candida carriage was significantly higher in Naswar users, particularly those with fungal infections of C. albicans, C. krusei, or both. These participants also exhibited elevated levels of salivary oxidative stress. Practical Implication: Public health interventions and oral health education programs should be implemented to raise awareness about the risks associated with Naswar and promote good oral hygiene practices among users. Conclusion: This study reveals significant differences in oral Candida carriage and salivary oxidative stress between Naswar users and non-users, indicating potential implications for the oral health of Naswar users. These findings underscore the need for larger prospective studies to validate the detrimental effects of Naswar use. Public health interventions targeting smokeless tobacco users should prioritize oral health promotion and emphasize the risks associated with Naswar consumption. Keywords: Candida species, smokeless tobacco, oral health, oxidative stress